Lakon Wayang Dewi Sinta Simbol Keteguhan Feminis sebagai Ide Penciptaan Karya Lukis - Arida Nafisah (Jurnal Pendidikan dan Penciptaan Seni, 2022)
The creation of this painting originated from the author's experience when discussing endless issues of women. Social issues regarding women are always updated in various issues ranging from discrimination, crime and injustice against women. In fact, this feminist issue has existed since time immemorial with the story of Dewi Shinta, who has always carried feminine values. The aim is to create paintings that have a feminist value concept in Dewi Shinta and create paintings through the process of selecting sketches, materials, manufacturing techniques, exploration, and presentation that have the meaning of feminist firmness values. The method used in this thesis is the method of making a thesis. In the realm of this creation process consists of several stages, namely the formation stage (Forming). Coloring (Colloring), Finishing (Finishing). The creators hope that this work can be used as inspiration to create works of art that are always updated. Conceptually, the creation of painting works wants to build a national cultural character that is increasingly fading through feminist values.